EFFECT OF ANGIOSPERMIC EPIPHYTES ON THE RELATIVE STATUS OF ERGOSTEROL AND ELECTROLYTE LEAKAGE IN FUNGAL PATHOGENS - BARKAH, HAMZAH JUMAH ESSA; LOKESH, S. (International Journal of Current Pharmaceutical Research, 2020)
Objective: In the present study, emphasis has been made to assay the antifungal activity of some angiospermic epiphytes like Cuscuta reflexa, Viscum orientale, Cymbidium bicolor, Bulbophyllum propinquum, Hoya ovalifolia and Dendrophthoe falcata. Methods: The antifungal activity due to epiphytes extracts was expressed in term of reduction in dry biomass of fungi based on the relationship of ergosterol content and electrolyte leakage in fungal pathogens viz., Colletotrichum dematium, Drechslera oryzae, Fusarium oxysporum and Fusarium solani treated with epiphytes extract. Results: Treated fungi showed increased in ergostesrol content and increased electrolyte leakage confirmed the pathetic situation of fungi; hence there was fungistatic effect, which was dose-dependent. Conclusion: The angiospermic epiphytes of selected species chosen for the study could be serves an alternative eco-friendly source to synthetic fungicides.